The Synergy of e-Procurement and e-Coupon Subsidies: An Innovation for Transparent Public Spending to Stimulate National Economic Circulation - Stephanus Goenawan (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2026)
The government is crucial in driving national economic growth through effective, transparent public spending strategies. This study examines two innovative approaches implemented by the government to strengthen public purchasing power and accelerate the circulation of money across various economic levels. First, implementing an electronic procurement system (e-procurement) ensures that goods and services are conducted openly, competitively, and accountably. This improves efficiency, reduces the risk of corruption, and maximizes the benefits of public spending for society. Second, the e-coupon-based consumption subsidy strategy directly incentivizes citizens, notably lower- and middle-income groups, to purchase essential goods or strategic services. This approach stimulates domestic consumption and revitalizes the retail and MSMEs sectors. Integrating e-procurement and e-coupons creates a dual effect: efficient public expenditure upstream and increased public consumption downstream. The analysis shows that this strategy enhances fiscal transparency, stimulates economic growth, and sustainably improves public welfare through widespread and equitable money circulation.